A qualitative study exploring patients experience of ACS and a structured approach to its management. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Waterfield, Kerry; Andrew, Inga; Macnaughton, Jane; Hawkins, Colette
Abstract : Background: Anorexia Cachexia syndrome (ACS) is a common and devastating condition in cancer patients. It is poorly defined and heterogeneous, with many difficulties in conducting research and translating those findings into practice. A literature review revealed that patients' experience of the care offered by healthcare professionals was generally negative. Professionals were seen to avoid the issue or offer scanty/ineffective advice. It was hypothesised that proactive, systematic management could overcome some of these barriers. This was seen in an interventional study of such an approach, QISAM (Quantifying the impact of Standardised Assessment and Management). Aims: The aim of this qualitative study was to increase understanding of the experience of ACS from the individual patient perspective and to determine how taking part in QISAM impacted upon this experience. It also aimed to determine why the intervention had been beneficial and help with the process of translating the results of that study into practice. Method: Ten patients suffering from ACS who had participated in QISAM were interviewed postintervention in their homes using a semistructured approach. Interviews were transcribed verbatim and analysed using an interpretative phenomenological approach. Results: A common experience of patients was a struggle with the lack of control or uncertainty they faced. The huge anxiety linked to ACS was also apparent. Participating in QISAM seemed to help patients regain a little of that sense of control as they learned to manage their symptoms and access help. The structured approach of QISAM, including the practical advice given, provided much needed reassurance. Conclusions: This study is the first to explore patient's experience of an intervention to address ACS. The results support previous findings of the significant impact of the condition. It suggests the benefit of the intervention was influenced by the fact that patients felt reassured and empowered.